Community Archives, Community Clouds: Enabling Digital Preservation for Small Archives - Hurley, Grant (Archivaria, 2016)
Small, local, independent, and oftentimes idiosyncratic, the many community archives across the globe are commonly considered the least prepared to undertake digital preservation activities. Taking up the concept of archives as a “place of preservation” and putting it in conversation with the distinct areas of scholarship on community archives and cloud computing, I argue that community archives are enabled by cloud-computing solutions to begin acquiring and preserving born-digital records. To do so means re-imagining the boundaries of where preservation takes place. I outline the concepts that define community archives in the Anglo-American context, discuss these ideas in relation to preservation and place, and connect them with a review of potential cloud-computing implementations and case examples for small archives. Embedded alongside records creators that represent a broad spectrum of organizations, people, and interests, community archives are ideally positioned to acquire the digital records of persons, businesses, and organizations that may escape large, institutionally based archives. The very distributed nature of community archives will enable them to contribute to a more networked approach to digital preservation, one that reflects the networked structure of cloud computing itself. RÉSUMÉ Petits, locaux, indépendants et souvent singuliers, les nombreux centres d’archives communautaires de par le monde sont communément considérés comme les moins bien préparés à entreprendre des activités de préservation numérique. En me servant du concept des archives comme « endroit de préservation » et en le plaçant en dialogue avec des champs distincts de la littérature scientifique par rapport aux archives communautaires et à l’informatique en nuage, je soutiens que les solutions de l’informatique en nuage ont permis aux archives communautaires de commencer à acquérir et à préserver les documents créés en format numérique. Arriver à le faire nécessite de repenser les limites de l’endroit où s’effectue la préservation. Je présente les concepts qui définissent les archives communautaires dans le contexte angloaméricain, je discute de ces idées en relation avec préservation et endroit, et je les lie à un survol des solutions potentielles de l’informatique en nuage et à des études de cas pour des petits centres d’archives. Bien ancrés comme ils le sont parmi les créateurs de documents qui représentent une grande étendue d’organisation, de personnes et d’intérêts, les centres d’archives communautaires sont très bien placés pour acquérir les documents numériques de personnes, de sociétés et d’organisations qui pourraient ne pas être ciblées par les grands centres d’archives institutionnalisés. La nature distribuée des archives communautaires leur permettra de contribuer davantage à une approche de réseautage pour effectuer la préservation numérique, une approche qui reflétera la structure de réseautage de l’informatique en nuage elle-même.